靶向淋巴细胞活化基因3(LAG-3)的核酸适体及其用途 (2024)
能够结合淋巴细胞活化基因3(LAG-3)的核酸适体及其用于调节免疫反应的用途。这种适体可包括富含G的基序，例如，GX1GGGX2GGTX3A(SEQ ID NO：1)，其中X1和X2各自独立地为G、C或不存在，以及X3为T或C，或L-(G)n-L'，其中n为5-9的整数(包含5和9)，且L和L'为具有互补序列的核苷酸区段。本文还提供了含有骨架部分的多聚体核酸适体，该骨架部分包括回文序列。 Nucleic acid aptamers capable of binding to lymphocyte activation gene 3 (LAG-3) and uses thereof for modulating immune responses. Such aptamers may comprise a G-rich motif, for example, GX1GGGX2GGTX3A (SEQ ID No: 1), in which each of X1 and X2 are independently G, C, or absent, and X3 is T or C, or L-(G)n-L′, in which n is an integer of 5-9 inclusive, and L and L′ are nucleotide segments having complementary sequences. Also provided herein are multimeric nucleic acid aptamers containing a backbone moiety, which comprises a palindromic sequence.